A systematic review and meta-analysis into the effect of lateral wedge arch support insoles for reducing knee joint load in patients with medial knee osteoarthritis. Issue 24 (June 2017) - Xing, Fei; Lu, Bin; Kuang, Ming-jie; Wang, Ying; Zhao, Yun-long; Zhao, Jie; Sun, Lei; Wang, Yan; Ma, Jian-xiong; Ma, Xin-long
Abstract: Objective: The aim of this study was to evaluate the immediate effects of lateral wedge arch support insoles (LWAS) on reducing the knee joint load in patients with medial knee osteoarthritis (OA) compared with an appropriate control. Methods: Databases including Medline, EMBASE, Web of Science, Wiley Online Library, Cochrane library, and Google Scholar were searched with no limits on study date or language, from the earliest available date to October 31, 2016. The included studies had to have the aim of reducing knee load and have an appropriate control. The main measured values were the first and second peak external knee adduction moments (EKAM) and the knee adduction angular impulse (KAAI). The random-effects model was used for analyzing the eligible studies. Results: Nine studies met the inclusion criteria with a total of 356 participants of whom 337 received LWAS treatment. The risk of methodological bias scores (quality index) ranged from 21 to 27 of 32. Treatment with LWAS resulted in statistically significant reductions in the first peak EKAM ( P  = .005), the second peak EKAM ( P  = .01), and the KAAI ( P  = .03). However, among trials in which the control treatment was control shoes, the LWAS showed no associations on the first peak EKAM ( P  = .10) or the KAAI ( P  =  .06); among trials in which the control treatment was neutral insoles, the LWAS showed no associations on the second peak EKAM ( P  = .21) or the KAAI ( P  = .23). At the same time, the LWAS showed no statistically significant reduction on the first peak EKAM ( P  = .39) when compared with flat insoles. Conclusion: Although meta-analysis outcomes of all studies indicated statistically significant associations between LWAS and reductions of the first peak EKAM, second peak EKAM and KAAI in people with medial knee OA while walking, different results existed in subgroups using various control conditions for comparison. These findings do not support the use of LWAS insoles for reducing knee load. An optimal LWAS treatment should provide the appropriate height of arch support and amount of lateral wedging. Further research should investigate the best combination of these 2 parameters to achieve efficacy without altered comfort. Abstract : Supplemental Digital Content is available in the text